ANALISIS KINERJA KEUANGAN MENGGUNAKAN RASIO PROFITABILITAS PADA BANK BRI YANG TERDAFTAR DI BEI PERIODE 2019 – 2023 - Silaban, Nurlela; Simamora, Dian Sinar; Marpaung, Angel Lasmauli; Togatorop, Pasia; Panjaitan, Ika Fitriani; Hasugian, Chrisnova; Siallagan, Hamonangan (Jurnal Akuntansi Kompetif, 2025)
Assessment of the financial level of a company can be done by analyzing the company's financial statements. To find out whether the company's financial condition is in good condition, various analyzes can be carried out, one of which is ratio analysis. The purpose of this study was to determine the financial performance of BRI Bank in terms of financial ratio analysis. The analysis method used is descriptive quantitative analysis using the measurement of profitability ratios. Research data and information obtained from the financial statements of Bank BRI listed on the IDX. Based on the profitability ratio of this study, the financial performance of BRI bank in 2019-2023 experienced a fairly good level when viewed from return on assets and return on equity in 2020 while in 2023 the profitability ratio value was in the highest position both in return on assets and return on equity. Keywords: Financial Performance, ROA, ROE, Bank BRI